2021
DOI: 10.1109/lra.2021.3061345
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Goal-Directed Oscillations in Articulated Soft Robots: The Point-To-Point Case

Abstract: Introducing elasticity in the mechanical design can endow robots with the ability of performing efficient and effective periodic motions. Yet, devising controllers that can take advantage of such elasticity is still an open challenge. This letter tackles an instance of this general problem, by proposing a control architecture for executing goal-oriented and efficient point-to-point periodic motions. This is achieved by (i) producing motor torques that excite intrinsic modal oscillations, and simultaneously (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…1 All authors are with the German Aerospace Center (DLR); Institute of Robotics and Mechatronics; Münchener Straße 20, 82234 Weßling, Germany. tasks in an industrial context [7]- [11]. Consequently, many algorithms have been recently proposed that stabilize nonlinear oscillations in mechanical systems.…”
Section: Introductionmentioning
confidence: 99%
“…1 All authors are with the German Aerospace Center (DLR); Institute of Robotics and Mechatronics; Münchener Straße 20, 82234 Weßling, Germany. tasks in an industrial context [7]- [11]. Consequently, many algorithms have been recently proposed that stabilize nonlinear oscillations in mechanical systems.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the system coupled the simple CPGs with the world, through the soft joints of the GummiArm, which drove the error signal used by the learning algorithm. Interestingly, Bonacchi et al ( 2021 ) have recently shown that the elasticity of a joint can be exploited to achieve point to point goal-directed periodic movement, by tuning the elasticity to shape the natural modes of the system. The GummiArm joints could serve well for future experiments in this direction.…”
Section: Resultsmentioning
confidence: 99%
“…f) E reaches [E − , E + ] asymptotically: The previous step of the proof implies that ā1 (x 1 (t), ẋ1 (t)) = 0, and ( 13) is equal to (7) for all the t > T . The manifold attractiveness follows from H3 and lemma 1, and in turn…”
Section: D) Energy Increases In Timementioning
confidence: 95%
“…where again we applied the chain rule and plugged in ( 6) and (7). Now, we exploit once more the tangency constraints ( 5), together with the definition of ∆ and the expression of its time derivative (9).…”
Section: Eigenmanifold Stabilizationmentioning
confidence: 99%
See 1 more Smart Citation